2016
DOI: 10.3109/14767058.2016.1173672
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postpartum glycemic control and risk of surgical site infection

Abstract: In our cohort of diabetic women who underwent cesarean delivery, immediate postoperative hyperglycemia was not associated with wound morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the study evaluating the relationship between postpartum glycemic control and SSI, mean blood glucose levels were higher in the SSI group. On the other hand, in the same study, they could not definitely show its association with SSI and finally reported that instantaneous increases in blood glucose levels were not predictive for SSI [8]. When patients with and without postoperative SSI following CS were compared, neither the frequency of diabetes mellitus nor GDM were significantly different from each other in another study [13].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In the study evaluating the relationship between postpartum glycemic control and SSI, mean blood glucose levels were higher in the SSI group. On the other hand, in the same study, they could not definitely show its association with SSI and finally reported that instantaneous increases in blood glucose levels were not predictive for SSI [8]. When patients with and without postoperative SSI following CS were compared, neither the frequency of diabetes mellitus nor GDM were significantly different from each other in another study [13].…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Haidar et al [2] reported the incidence of SSI following CS as 6.5%. In the study of Johnston et al [8], SSI following CS was 16.5%. The data from our country about CS-related SSI is quite limited.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, hyperglycemia has been shown to be associated with SSI not only in diabetic patients (with constant hyperglycemia) but also in those patients who develop stress hyperglycemia after surgery [11], and control of blood glucose levels can reduce SSI by 50% [12]. Blood glucose levels impact wound healing by interfering with angiogenesis through modulation of growth factors and cytokines such as vascular endothelial growth factor (VEGF), transforming growth factor beta (TGF-b), platelet-derived growth factor (PDGF), and soluble fms-like tyrosine kinase 1 (sFlt-1) [13,14]. Authors have confirmed that these alterations in wound healing are increasingly complex and can also involve phagocytosis, chemotaxis, blood vessel adhesion, bactericidal activity of granulocytes, collagen synthesis, and fibroblast proliferation.…”
Section: Future Directions To Limit Surgical Site Infectionsmentioning
confidence: 99%